Newly- and early-immigrated second-language students’ knowledge of arithmetic syntax - Petersson, Jöran (NOMAD Nordic Studies in Mathematics Education, 2018)
The present study investigated how 259 Swedish, grade 9 students, of whom 90 had an immigrant background, achieved on twelve written test items in the content area of number. Four of the twelve test items required good knowledge of arithmetic syntax, such as when it was appropriate to apply order-of-operation rules and the associative and distributive laws of arithmetic operations. On these four test items, the most-recently arrived students showed on average significantly more knowledge than the students who had immigrated when they were younger and had participated in Swedish schools for longer periods of time. The outcome suggests that these two groups of immigrant students in later school years should be considered as separate sub-categories of second-language students when it comes to teaching, assessment and research.